Pengaruh Semangat Kerja, Kompetensi Dan Disiplin Kerja Terhadap Efektivitas Kerja Pada PT. Happy Jaya Plastik - M Abel Pradana Putra; Ahmad Jauhari; Nur Hidayati (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This research aims to determine the influence of the variables work enthusiasm (X1), competence (X2), and work discipline (X3) on work effectiveness (Y) at PT Happy Jaya Plastik. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. Sample selection used the saturated sampling method, the number of samples in the study was 60 respondents at PT Happy Jaya Plastik. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= 10.489 + 0.342X1 + 0.400X2 + 0.347X3 and the t test results of the variables work enthusiasm, competence and work discipline had a partially significant effect on work effectiveness with a sig < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that work enthusiasm, competence and work discipline simultaneously have a significant effect on the work effectiveness of PT Happy Jaya Plastik.